Deformation assisted joining of sheets to rods by indentation and injection. (May 2021) - Alves, L.M.; Afonso, R.M.; Brosius, A.; Martins, P.A.F.
Abstract: This paper presents a deformation assisted joining process for fixing a sheet to a rod away from the rod ends, at room temperature. The process requires machining a rectangular cross-section slot in the rod so that material from the sheet can be locally indented and injected into the slot to produce a form-fit joint. Selected examples retrieved from experimentation and finite element simulation allow understanding the overall deformation mechanics, identifying the major operating parameters, and establishing design guidelines for both punches and slots. Detailed information on the punch strokes and geometries to obtain sheet-rod connections with an adequate filling of the slots and without excessive reduction of the cross-sectional shear length are provided. The new proposed process was built upon modification of an earlier development for fixing thick hubs to shafts (or, rods) and is aimed at satisfying the challenges and requirements posed by thin sheets. Emphasis is placed on lowering the forming forces and facilitating injection and filling of the slots so that thin sheets can effectively be fixed to rods. Pull-out destructive tests performed on sheet-rod connections away from the rod ends confirm the good performance of the form-fit joints produced by the new proposed process.